Aqueous zinc ion battery electrolyte and application thereof
By adding quaternary ammonium fluoride to the electrolyte of the aqueous zinc ion battery, the battery short circuit problem caused by the growth of zinc negative electrode dendrites is solved, and the battery life and stability are significantly improved.
Patent Information
- Application Number
- CN202510019014.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
The battery short circuit problem caused by the growth of zinc negative electrode dendrites in aqueous zinc ion batteries affects the battery's Coulomb efficiency and life cycle.
The addition of quaternary ammonium fluoride to the electrolyte of the aqueous zinc ion battery inhibits the effect of hydrogen bonds in the solution, promotes the uniform deposition and peeling of zinc ions on the negative electrode surface, and thus inhibits the formation and growth of zinc dendrites.
Significantly improve the short circuit time of zinc negative electrode, extend the device life of aqueous zinc ion batteries, and significantly improve the cycling performance and stability of the battery.
Smart Images

Figure BDA0005230906130000051 
Figure BDA0005230906130000061 
Figure BDA0005230906130000062
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new energy materials, and specifically relates to an aqueous zinc ion battery electrolyte and an application thereof. Background Art
[0002] With the excessive consumption of non-renewable energy such as oil, the rational development and utilization of renewable energy such as solar energy and wind energy is becoming increasingly important. However, various renewable energy sources are restricted by factors such as geography and environment, and there are serious randomness and intermittency. Therefore, it is crucial to achieve optimal management and large-scale storage of energy. Secondary batteries are generally considered to be a powerful carrier for realizing large-scale energy storage technology, but the lithium-ion batteries that currently dominate the commercial mainstream have great limitations in the field of large-scale energy storage due to their low safety and high cost. On the contrary, aqueous batteries are regarded as one of the most promising large-scale energy storage technologies because of their advantages such as low cost, high safety, environmental friendliness and long cycle life. However, the commercial aqueous batteries currently on the market, such as nickel-hydrogen batteries and lead-acid batteries, are subject to the disadvantages of low energy density and short cycle life, and cannot meet the application requirements of large-scale energy storage technology. Therefore, it is urgent to develop low-cost, high-safety, high-energy-density and long-cycle-life aqueous batteries.
[0003] At present, lithium-ion batteries have been widely used in energy storage power stations, new energy vehicles and various other electronic devices. However, lithium-ion batteries have problems such as fire and explosion, high cost, resource shortage and high cost of waste disposal, which restrict the application of lithium-ion batteries in the field of large-scale energy storage. Aqueous zinc batteries are one of the most promising large-scale energy storage devices due to their high specific capacity (820mAh / g), low redox point (-0.76V vs SHE), high safety, non-toxicity and significant economic benefits. However, the zinc anode in the aqueous electrolyte has zinc dendrites and side reactions, resulting in low coulombic efficiency and short life cycle of the battery. Since the electrolyte plays a key role in the stripping / deposition process, it is a problem to be solved to provide an aqueous zinc-ion battery electrolyte formula for solving the battery short circuit problem caused by zinc negative electrode dendrite growth. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide an aqueous zinc ion battery electrolyte and its application. The aqueous zinc ion battery electrolyte provided by the present invention can solve the battery short circuit problem caused by the growth of zinc negative electrode dendrites.
[0005] The invention provides an aqueous zinc ion battery electrolyte comprising quaternary ammonium salt fluoride.
[0006] Preferably, the quaternary ammonium salt fluoride includes one or more combinations of tetramethylammonium fluoride, tetraethylammonium fluoride, tetrabutylammonium fluoride, tetraphenylammonium fluoride, tetraoctylammonium fluoride, tetra(2-hydroxypropyl)ammonium fluoride, tetra(3-hydroxypropyl)ammonium fluoride, methyltriethylammonium fluoride, methyltripropylammonium fluoride, methyltributylammonium fluoride, phenyltrimethylammonium fluoride, phenyltriethylammonium fluoride, phenyltripropylammonium fluoride, phenyltributylammonium fluoride, dimethyldibutylammonium fluoride, tripropylmethylammonium fluoride, trioctylmethylammonium fluoride, trinonylmethylammonium fluoride, benzyltriethylammonium fluoride, benzyltripropylammonium fluoride, and benzyltributylammonium fluoride.
[0007] Preferably, the amount of the quaternary ammonium salt fluoride added to the electrolyte is 0.001 to 10.0 mol / L.
[0008] Preferably, an electrolyte and a solvent are also included.
[0009] Preferably, the electrolyte includes one or a combination of at least two of zinc trifluoromethanesulfonate, zinc sulfate, zinc nitrate, zinc chloride, zinc hypochlorite, zinc acetate, zinc citrate, zinc perchlorate, and zinc bis(trifluoromethanesulfonyl)imide.
[0010] Preferably, the concentration of the electrolyte in the electrolyte is 0.1 to 20.0 mol / L.
[0011] Preferably, the solvent is selected from deionized water.
[0012] The present invention also provides an aqueous zinc ion battery, comprising the above electrolyte.
[0013] Preferably, the aqueous zinc ion battery further includes a positive electrode, a negative electrode, and a separator.
[0014] Aqueous zinc ion battery, wherein the positive electrode is selected from zinc sheet;
[0015] The negative electrode is selected from one of zinc sheet, aluminum sheet, graphite, silver sheet and platinum sheet;
[0016] The diaphragm is selected from one of glass fiber, polypropylene diaphragm, polyethylene diaphragm and nanoporous diaphragm.
[0017] Compared with the prior art, the present invention provides an aqueous zinc ion battery electrolyte, comprising quaternary ammonium salt fluoride. The present invention adds the quaternary ammonium salt fluoride to the aqueous zinc ion battery electrolyte, which can inhibit the effect of hydrogen bonds in the solution, facilitate the uniform deposition and stripping of zinc ions on the negative electrode surface, thereby inhibiting the formation and growth of zinc dendrites. In addition, the short-circuit time of the zinc negative electrode is greatly improved, and the device life of the aqueous zinc ion battery is improved. In addition, the formula has a small usage amount, is easy to use, and has little pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a scanning electron microscope photo of the polished zinc foil surface;
[0019] Figure 2 Scanning electron micrograph of the zinc foil surface after 50 cycles with the addition of ZnSO4-based electrolyte;
[0020] Figure 3 Scanning electron micrograph of the zinc foil surface after 50 cycles with the addition of 0.3 mol / L experimental electrolyte;
[0021] Figure 4 Symmetric cells were assembled using 2 mol / L zinc sulfate electrolyte and 2 mol / L zinc sulfate electrolyte containing different concentrations of tetramethylammonium fluoride. 2 Current density and 1mAh / cm 2 Cycling performance diagram at capacity density;
[0022] Figure 5 The Tafel curves were obtained by testing the electrochemical workstation using 2 mol / L zinc sulfate electrolyte containing different concentrations of tetramethylammonium fluoride. DETAILED DESCRIPTION
[0023] The invention provides an aqueous zinc ion battery electrolyte comprising quaternary ammonium salt fluoride.
[0024] In some specific embodiments of the present invention, the quaternary ammonium salt fluoride comprises one or more combinations of tetramethyl ammonium fluoride, tetraethyl ammonium fluoride, tetrabutyl ammonium fluoride, tetraphenyl ammonium fluoride, tetraoctyl ammonium fluoride, tetra(2-hydroxypropyl) ammonium fluoride, tetra(3-hydroxypropyl) ammonium fluoride, methyl triethyl ammonium fluoride, methyl tripropyl ammonium fluoride, methyl tributyl ammonium fluoride, phenyl trimethyl ammonium fluoride, phenyl triethyl ammonium fluoride, phenyl tripropyl ammonium fluoride, phenyl tributyl ammonium fluoride, dimethyl dibutyl ammonium fluoride, tripropyl methyl ammonium fluoride, trioctyl methyl ammonium fluoride, trinonyl methyl ammonium fluoride, benzyl triethyl ammonium fluoride, benzyl tripropyl ammonium fluoride, and benzyl tributyl ammonium fluoride. Preferably, the quaternary ammonium salt fluoride is selected from tetramethyl ammonium fluoride, tetraethyl ammonium fluoride, tetrabutyl ammonium fluoride, tetraoctyl ammonium fluoride, tetraphenyl ammonium fluoride, and methyl triethyl ammonium fluoride.
[0025] The quaternary ammonium salt fluoride electrolyte formula has a stronger solvation effect than water, which is beneficial to adjust the solvation shell of zinc ions and inhibit side reactions, thereby extending the service life of the zinc negative electrode.
[0026] In the present invention, the amount of the quaternary ammonium fluoride added to the electrolyte is 0.001 to 10.0 mol / L, and can be 0.001, 0.005, 0.01, 0.05, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or any value between 0.001 and 10.0 mol / L.
[0027] In the present invention, the aqueous zinc ion battery electrolyte further comprises an electrolyte and a solvent.
[0028] The electrolyte includes one or a combination of at least two of zinc trifluoromethanesulfonate, zinc sulfate, zinc nitrate, zinc chloride, zinc hypochlorite, zinc acetate, zinc citrate, zinc perchlorate, and zinc bis(trifluoromethanesulfonyl)imide, preferably zinc sulfate.
[0029] The concentration of the electrolyte in the electrolyte is 0.1 to 20.0 mol / L, and can be 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or any value between 0.1 and 20.0 mol / L.
[0030] In the present invention, the solvent of the aqueous zinc ion battery electrolyte is selected from deionized water.
[0031] The present invention also provides an aqueous zinc ion battery, comprising the above electrolyte.
[0032] The aqueous zinc ion battery also includes a positive electrode, a negative electrode and a separator.
[0033] The present invention does not particularly limit the types of the positive electrode, negative electrode and separator of the aqueous zinc ion battery. The positive electrode, negative electrode and separator that can be used for aqueous zinc ion batteries that are well known to those skilled in the art can be used.
[0034] Preferably, the positive electrode is selected from zinc sheet;
[0035] The negative electrode is selected from one of zinc sheet, aluminum sheet, graphite, silver sheet and platinum sheet, preferably zinc sheet;
[0036] The diaphragm is selected from one of glass fiber, polypropylene diaphragm, polyethylene diaphragm and nanoporous diaphragm, preferably glass fiber.
[0037] The invention adds the quaternary ammonium salt fluoride to the aqueous zinc ion battery electrolyte, which can inhibit the effect of hydrogen bonds in the solution, facilitate the uniform deposition and stripping of zinc ions on the negative electrode surface, thereby inhibiting the formation and growth of zinc dendrites. Further, the short-circuit time of the zinc negative electrode is greatly improved, and the device life of the aqueous zinc ion battery is improved. In addition, the formula is used in a small amount, is easy to use, and has little pollution.
[0038] The results show that compared with an electrolyte without adding quaternary ammonium salt fluoride, the battery life is greatly improved when using the electrolyte of the present invention, and the short circuit time can be increased from a maximum of 100 hours to more than 2500 hours, an improvement of more than 2500%.
[0039] In order to further understand the present invention, the aqueous zinc ion battery electrolyte and its application provided by the present invention are described below in conjunction with embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0040] Example 1
[0041] Solid zinc sulfate heptahydrate is dissolved in deionized water, and stirred and dissolved at room temperature to prepare a basic electrolyte with a concentration of 2 mol / L.
[0042] Weigh an appropriate amount of tetramethylammonium fluoride (NMe4F) solid and dissolve it in the above 10 mL of 2M ZnSO4 basic electrolyte. Ultrasonicate and stir evenly for 50 min until it is completely dissolved. Prepare 0 mol / L, 0.02 mol / L, 0.04 mol / L, 0.06 mol / L, 0.06 mol / L, 0.06 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.6 mol / L, and 1.0 mol / L as experimental electrolytes, respectively.
[0043] Take a 100 micron thick zinc foil and polish it with 2000 mesh sandpaper, cut it into a small disc with a diameter of 12mm, take glass fiber as a separator, cut it into a small disc with a diameter of 14mm, take 60ul of the prepared experimental electrolyte and add it to the glass fiber, assemble it into a CR2032 button-type symmetrical battery in the order of positive electrode shell, zinc sheet, separator, electrolyte, zinc sheet, gasket, shrapnel, and negative electrode shell. The battery life in different electrolytes was evaluated in the "LANHE" series battery test system (Wuhan Landian Electronics Co., Ltd.).
[0044] Figure 1 This is a scanning electron microscope photo of the polished zinc foil surface. Figure 2 Scanning electron micrograph of the zinc foil surface after 50 cycles with the addition of ZnSO4-based electrolyte. Figure 3 Scanning electron microscope image of the zinc foil surface after 50 cycles with the addition of 0.3 mol / L experimental electrolyte.
[0045] Depend on Figure 1 to Figure 3 It can be seen that the battery prepared by the electrolyte provided in Example 1 can inhibit the formation of zinc dendrites, thereby improving the battery life.
[0046] Figure 4Symmetric cells were assembled using 2 mol / L zinc sulfate electrolyte and 2 mol / L zinc sulfate electrolyte containing different concentrations of tetramethylammonium fluoride. 2 Current density and 1mAh / cm 2 Cycling performance diagram at capacity density. Figure 4 It can be seen that the zinc foil negative electrode has the best cycling performance in 2 mol / L zinc sulfate electrolyte with 0.3 mol / L tetramethylammonium fluoride added, and the symmetrical battery life exceeds 2500 hours.
[0047] Figure 5 The Tafel curves are obtained by using 2 mol / L zinc sulfate electrolyte with different concentrations of tetramethylammonium fluoride in an electrochemical workstation. Figure 5 It can be seen that the corrosion potential has obvious movement, and the potential movement is most obvious when the formula concentration reaches 0.3 mol / L.
[0048] Example 2
[0049] Solid zinc sulfate heptahydrate is dissolved in deionized water, and stirred and dissolved at room temperature to prepare a basic electrolyte with a concentration of 2 mol / L.
[0050] Weigh appropriate amounts of tetramethylammonium fluoride, tetraethylammonium fluoride, tetrabutylammonium fluoride, tetraoctylammonium fluoride, tetraphenylammonium fluoride, and methyltriethylammonium fluoride solids, dissolve them in 10 mL of the above-mentioned 2M ZnSO4 basic electrolyte and prepare them to 0.3 mol / L. Stir them evenly with ultrasonic for 50 min until they are completely dissolved, and obtain 6 portions of experimental electrolyte.
[0051] Take a 100 micron thick zinc foil and polish it with 2000 mesh sandpaper, cut it into a small disc with a diameter of 12mm, take glass fiber as a separator, cut it into a small disc with a diameter of 14mm, take 60ul of the prepared experimental electrolyte and add it to the glass fiber, assemble it into a CR2032 button-type symmetrical battery in the order of positive electrode shell, zinc sheet, separator, electrolyte, zinc sheet, gasket, shrapnel, and negative electrode shell. The battery life in different electrolytes was evaluated in the "LANHE" series battery test system (Wuhan Landian Electronics Co., Ltd.).
[0052] Table 1
[0053]
[0054]
[0055] Comparative Example
[0056] Dissolve zinc sulfate heptahydrate solid in deionized water, stir and dissolve at room temperature to prepare a basic electrolyte with a concentration of 2 mol / L. Take a 100-micron-thick zinc foil and polish it with 2000-grit sandpaper, cut it into a small disc with a diameter of 12 mm, take glass fiber as a diaphragm, cut it into a small disc with a diameter of 14 mm, take 60ul of the prepared ZnSO4-based electrolyte and add it to the glass fiber, and assemble it into a CR2032 button-type symmetrical battery in the order of positive electrode shell, zinc sheet, diaphragm, electrolyte, zinc sheet, gasket, shrapnel, and negative electrode shell. The battery life in different electrolytes was evaluated in the "LANHE" series battery test system (Wuhan Landian Electronics Co., Ltd.).
[0057] Table 2
[0058]
[0059] According to tests, the aqueous zinc ion battery electrolyte provided by the present invention can significantly prolong the short-circuit time of the zinc negative electrode; according to its functions and effects, the aqueous zinc ion battery electrolyte can improve the stability of the deposition and stripping of the aqueous zinc ion battery.
[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An aqueous zinc ion battery electrolyte, characterized in that Includes quaternary ammonium fluorides.
2. The electrolyte according to claim 1, characterized in that The quaternary ammonium salt fluoride includes one or more combinations of tetramethylammonium fluoride, tetraethylammonium fluoride, tetrabutylammonium fluoride, tetraphenylammonium fluoride, tetraoctylammonium fluoride, tetra(2-hydroxypropyl)ammonium fluoride, tetra(3-hydroxypropyl)ammonium fluoride, methyltriethylammonium fluoride, methyltripropylammonium fluoride, methyltributylammonium fluoride, phenyltrimethylammonium fluoride, phenyltriethylammonium fluoride, phenyltripropylammonium fluoride, phenyltributylammonium fluoride, dimethyldibutylammonium fluoride, tripropylmethylammonium fluoride, trioctylmethylammonium fluoride, trinonylmethylammonium fluoride, benzyltriethylammonium fluoride, benzyltripropylammonium fluoride, and benzyltributylammonium fluoride.
3. The electrolyte according to claim 1, characterized in that The amount of the quaternary ammonium salt fluoride added to the electrolyte is 0.001 to 10.0 mol / L.
4. The electrolyte according to claim 1, characterized in that Also included are electrolytes and solvents.
5. The electrolyte according to claim 4, characterized in that The electrolyte includes one or a combination of at least two of zinc trifluoromethanesulfonate, zinc sulfate, zinc nitrate, zinc chloride, zinc hypochlorite, zinc acetate, zinc citrate, zinc perchlorate, and zinc bis(trifluoromethanesulfonyl)imide.
6. The electrolyte according to claim 4, characterized in that The concentration of the electrolyte in the electrolyte is 0.1-20.0 mol / L.
7. The electrolyte according to claim 4, characterized in that The solvent is selected from deionized water.
8. An aqueous zinc ion battery, characterized in that: The electrolyte comprising any one of claims 1 to 7.
9. The aqueous zinc ion battery according to claim 8, characterized in that: It also includes a positive electrode, a negative electrode, and a separator.
10. The aqueous zinc ion battery according to claim 9, characterized in that: The positive electrode is selected from a zinc sheet; The negative electrode is selected from one of zinc sheet, aluminum sheet, graphite, silver sheet and platinum sheet; The diaphragm is selected from one of glass fiber, polypropylene diaphragm, polyethylene diaphragm and nanoporous diaphragm.